IGBT Comparison for Optimized Switching Behavior in the SiC/Si-Hybrid Switch - Amler, Adrian; Heckel, Thomas; Ruppert, Daniel; Retter, Cornelius; März, Martin (2025 IEEE Applied Power Electronics Conference and Exposition (APEC), 2025)
The parallel connection of Si-IGBTs and SiC-MOSFETs in a so-called hybrid switch offers new degrees of freedom to optimize the efficiency of bridge-type inverters and converters. By separately controlling the parallel devices with a gate delay, the switching performance can be improved to resemble that of the superior MOSFET. It is known that the optimal switching strategy depends on the operating point (temperature, current) and the hybrid switch design (chip area ratio, gate resistance). Additionally, the switching and conduction behavior changes drastically when using different IGBT technologies and devices. The comprehensive experimental study performed for this paper demonstrates that the IGBT technology used has a strong influence on the system efficiency as a result of its forward characteristics and its turn-OFF performance and gives an overview of the relevant dependencies. Different established and state-of-the-art IGBTs are tested in a double pulse setup and compared regarding their switching performance in the hybrid switch. It is shown that the hybrid switch variants can achieve from up to 54 % to 71 % system loss reduction compared to a standalone IGBT system depending on the device selection. It thus performs on-par with SiC MOSFETs under comparable operating condition